SCLF algorithm for polar code based on GRU network assistance and path metric exchange - Jun LI; Lejia ZHOU; Zhengquan LI; Ru JI; Jintao ZHU; Xingxin LIU; Ziyi LIU (Tongxin xuebao)
In order to solve the problems of low transmission performance, inaccurate flip set construction and high complexity of existing polar codes successive cancellation list bit-flip (SCLF) algorithms, a SCLF algorithm for polar codes based on GRU network assistance and path metric exchange was proposed.First the decoding state was redivided, and a bit-flip strategy was proposed by combining the ideas of path metric exchange and reverse judgment.Secondly, a flip set construction method was proposed by training the GRU network to locate the first erroneous bit in the decoding.Finally, a multi-bit flipping rule was proposed by sorting the path metric for each low-order flip and fixing the low-order reliable bits before performing the high-order flip.Simulation results show that compared with the existing SCLF algorithms, the proposed algorithm improves the accuracy of identifying the first error bit by 18～24% at low signal noise ratio.Under single-bit and multi-bit flipping, the proposed algorithm has a performance gain of up to 0.3 dB and 0.2 dB, respectively, and the online decoding complexity is lower.